2020
DOI: 10.1177/0268580920912970
|View full text |Cite
|
Sign up to set email alerts
|

The reincarnation of work motivation: Millennials vs older generations

Abstract: This study examines generational differences in valuing the sources of motivation in workplace behaviour between millennials and older generations, with a view to assist managers in making employment decisions and maintaining multigenerational staff in the services sector. Based on systematically sampled data, the authors used Gagné et al.’s Multidimensional Work Motivational Scale (MWMS) to measure the different facets of work motivators alongside a three-item measure of employee overall work motivation (desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 53 publications
0
44
0
2
Order By: Relevance
“…Another study was carried out to examine generational differences in valuing the sources of motivation in workplace behavior between millennials and older generations. The results showed that both extrinsic regulation-material and identified regulation are valued more by millennials compared to older generations, while extrinsic regulation-social and introjected regulation are valued less by millennials compared to older generations (Mahmoud et al, 2020).…”
Section: Reinforcement (By Skinner)mentioning
confidence: 91%
“…Another study was carried out to examine generational differences in valuing the sources of motivation in workplace behavior between millennials and older generations. The results showed that both extrinsic regulation-material and identified regulation are valued more by millennials compared to older generations, while extrinsic regulation-social and introjected regulation are valued less by millennials compared to older generations (Mahmoud et al, 2020).…”
Section: Reinforcement (By Skinner)mentioning
confidence: 91%
“…The presence of three psychological needs of competence, relatedness and autonomy fulfils the requirements for strong intrinsic motivation (Ryan & Deci, 2000). Intrinsically motivated individuals are motivated by self‐satisfaction and thus are content to perform according to organizational standards (Mahmoud, Reisel, Grigoriou, Fuxman & Mohr, 2020). When intrinsic motivation is challenged by job insecurity, particularly through impairment of individual autonomy, it leads to decreased job satisfaction because employees perceive a threat.…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Results show that the most significant factor for the age group up to 30 years is independence, flexibility, responsibility and other employment benefits such as some cultural or sports activities. This age group is not simply motivated by monetary reward [20]. These employees want fulfilment and autonomy in their work [21] and they dislike being controlled [20].…”
Section: Resultsmentioning
confidence: 99%
“…This age group is not simply motivated by monetary reward [20]. These employees want fulfilment and autonomy in their work [21] and they dislike being controlled [20]. The most significant factor for the age group up to 50 years is financial motivation.…”
Section: Resultsmentioning
confidence: 99%